Analisis Pengelolaan Keuangan Daerah Pada Dinas Tenaga Kerja Dan Transmigrasi Provinsi Sulawesi Utara - elisabeth Tampang (Jurnal LPPM Bidang EkoSosBudKum (Ekonomi,Sosial,Budaya, dan Hukum), 2022)
Analysis of Regional Financial Management is all the rights and obligations of the region in the context of the administration of regional governments which can be valued in money including all forms of wealth related to the rights and obligations of the region. The Department of Manpower and Transmigration of North Sulawesi Province is one of the local government departments engaged in manpower, community empowerment and transmigration. This study aims to determine whether the Regional Financial Management in the Manpower and Transmigration Office of North Sulawesi Province is in accordance with Permendagri Number 77 of 2020 concerning Regional Financial Management in which there are all activities including planning, implementation, administration, and accountability. The analytical method used in this research is descriptive method in which the purpose of each data collected is analyzed then drawn a conclusion and the type of research used is descriptive qualitative. The results obtained indicate that the Analysis of Regional Financial Management at the Manpower and Transmigration Office of North Sulawesi Province is in accordance with the Regulation of the Minister of Home Affairs Number 77 of 2020 concerning Regional Financial Management